Efficient microwave-assisted hydrothermal synthesis of CuO sea urchin-like architectures via a mesoscale self-assembly - Volanti, Diogo P. [UNESP]; Orlandi, Marcelo Ornaghi [UNESP]; Andres, Juan; Longo, Elson [UNESP] (Royal Soc Chemistry, 2010)
For the first time, we provide evidence for both heterogeneous nucleation at the mesoscopic scale and the progression of the non-classical crystallization process during the microwave synthesis of cupric oxide (CuO) with sea urchin-like morphology. This work sheds light on the general mechanism of the growth of CuO architectures.